Plaza Rally #1 - Spring 1971 (1971)
[00:10] Raymond DeGroote, leader of SNAP, along with other student groups, asks Cal Poly President Robert E. Kennedy to answer questions about controversies on campus [01:00] DeGroote introduces the students representing the various organizations [01:19] Kennedy says a few statements about the format and major issues of the discussion before the discussion begins. [01:53] Kennedy says the students' main issues they wanted to talk about are foreign student tuition, Vrana case, Dr. Rizzo case, and the resident halls open/closed door controversy [03:57] Hasan Fahdrad, Leader of Iranian Student Association, asks Kennedy questions about foreign student tuition and other issues related to foreign students [05:30] Kennedy explains the technicalities of the out of state and foreign student tuition fee increases [07:12] Kennedy answers questions about foreign students night performance [09:31] John Mason, President of the Ecology Action Committee, asks questions about Professor Vrana's evaluation for tenure [10:10] Kennedy says Vrana was first denied tenure in 1969, but given a 5th year of employment and was not to be evaluated in the 5th year [11:55] Kennedy tells the story of Vrana's case chronologically [13:40] Kennedy tells of the University accreditors for the school of engineering saying that not enough instructors in the physics department had Doctorates to receive accreditation in the future [15:20] Kennedy says he could not give any more members of the department tenure until they had received the Doctorate [15:57] Kennedy reaffirms that this was the only reason Vrana was not given tenure, not other issues [16:20] Kennedy says Vrana filed a grievance and was sat before a board chosen by the academic senate who decided he should not be given tenure [18:56] Kennedy tells the manner in which he agreed to offer tenure to Vrana if he attains his Doctorate [21:09] Mason asks Kennedy why instructors in the English and Business departments were granted tenure with only Bachelor's degrees [21:26] Kennedy says that each department has its own minimum academic requirements for a faculty member to be granted tenure [22:58] Kennedy says that Clyde Fisher gave him the recommendation to not grant tenure to Vrana long before Vrana spoke against the SLO County Development Association [23:12] cut between side A and side B [23:50] Kennedy says that he and the faculty department agreed when Vranna gets his Doctorate he will be offered employment at the same position he currently holds [24:22] Kennedy states that it is not up to the president to give tenure, but the Board of Trustees operating within the rules of regulations regarding tenure [25:10] Kennedy reaffirms that Vrana is assured a job when he comes back but Kennedy cannot legally give instant tenure [26:16] Vranna says his letter from Kennedy does say he would reemployed but did not mention tenure upon return [26:34] Kennedy gives same reply as earlier, that he would give tenure if legally possible [28:57] Kennedy says that faculty members should abide by the political code of ethics and limitations set by the Academic Senate and The American Association of College and University Professors [29:39] Kennedy emphasizes faculty responsibility in connection with freedom [31:25] Kennedy explains why the American Legion article was in Rizzo's personnel file [34:12] DeGroote asks Kennedy to denounce the American Legion article quoting Rizzo's comment from the Mustang Daily were the same as what emanates from Hanoi, Vietnam [35:00] DeGroote reads the article from the American Legion about a petition from Cal Poly Faculty to President Nixon which features quotes from Rizzo about US involvement in Vietnam [37:47] Rizzo asks Kennedy if he will publicly denounce the line in the American Legion article that states Rizzo's line emanates from Hanoi [39:05] Kennedy says he cannot denounce the line because he is not sure if it has never been said by someone who is in support of communism [39:18] Kennedy says the question is unfair because he cannot denounce only one portion of a statement [40:03] DeGroote asks why instructors cannot sit in on their own evaluation meetings [40:25] Kennedy says each department has specific procedures for evaluations [41:25] Dr. Ericson, Dean of the School of Communicative Arts and Humanities, states that the evaluation committee did not know about the American Legion newsletter and so it was not part of their evaluation of Rizzo [41:47] Ericson says that it was his own responsibility to put things in personnel files and it is does not matter if President feels they are appropriate or not [42:37] Ericson states that there is a letter from a similar organization in his own file at Central Washington State College from debating against US involvement in Vietnam that squarely lists him as communist [44:27] Kennedy explained the procedure that Rizzo went through in his grievance and case evaluation process [45:35] Kennedy says that the department procedure excludes the people being considered to be involved with the tenured members in the meeting unless they are called in to the evaluation meeting by the members [47:45] Ericson talks about Rizzo's political activities in his first year teaching [49:14] Ericson says Rizzo's department voted him to be retained and promoted after his first year teaching [50:03] Ericson states Rizzo refused to teach courses assigned by his department head in his second year teaching [51:04] Ericson states that any instructor, even with tenure, who refuses to teach freshman courses will not receive his support for retention